Artikel Perbandingan Kurikulum Pendidikan Indonesia dengan Negara Malaysia, Singapura, Korea Selatan, Jepang dan Finlandia - Haryanti, Tutik; Karim, M. Nazir (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Each country has its own national education system, which is adapted to the national philosophical background, policies and strategies, which are also influenced by the state structure adopted and the goals to be achieved within the framework of the nation and state. One effort to improve the quality of a country's education is with a curriculum policy. Therefore, this article aims to analyze education curriculum policies in Indonesia in terms of comparison with five countries, namely Malaysia, Singapore, South Korea, Japan and Finland. The method used is literature review. From the results of data analysis, it was found that curriculum policy in Indonesia is still far behind those of the five countries, so there is a need for changes in the curriculum regulations established by the Indonesian government. The current curriculum policy still has not achieved the goals of the national education system.